The asymptomatic bacteriuria in the patients with epilepsy: A cross-sectional study - Yu-Shiue Chen; Tzu-Ping Weng; Ming-Chi Lai; Chin-Wei Huang (Heliyon)
Background: Epilepsy is a chronic neurological disorder characterized by repetitive unprovoked seizures. While certain anti-seizure medications have been linked to urinary tract infections, limited information exists on the occurrence and risk factors of asymptomatic bacteriuria (ASB) in individuals with epilepsy. This study aims to investigate the prevalence and factors associated with ASB in patients with epilepsy. Method: A cross-sectional study was conducted, enrolling patients with epilepsy and healthy adults as controls. All participants underwent urine analyses during follow-ups at an epilepsy special clinic. Data on epilepsy-related factors were thoroughly collected and analyzed. Descriptive statistics and a logistic regression model were employed to identify the prevalence and risk factors of ASB in patients with epilepsy. Results: The study encompassed 200 patients with epilepsy, compared to 100 healthy controls. The prevalence of ASB in the epilepsy group was significantly higher than in the healthy controls (34.0 % versus 16.2 %, p = 0.001). The logistic regression model identified factors statistically associated with ASB in epilepsy, including gender (female) (p < 0.001), proteinuria (p = 0.021), and the use of oxcarbazepine (p = 0.011). Interestingly, lamotrigine demonstrated a protective effect against ASB (p = 0.023), along with age (p = 0.015) in this study. Moreover, patients with and without ASB exhibited a similar rate of 12 months of seizure freedom. Conclusion: The prevalence of ASB is elevated in epilepsy, with identified risk factors including gender (female), proteinuria, and the use of the anti-seizure medication oxcarbazepine. Lamotrigine was found to be protective. These findings underscore the importance of clinician awareness, and careful monitoring of anti-seizure medication therapy.